Room temperature oxide-film formation by oxygen dissolution induced surface directed spinodal decomposition in stainless steel. (15th April 2020) - Sasidhar, K.N.; Meka, S.R.
Highlights: Thermodynamic analysis of oxide film formation in stainless steel has been performed. Role of surface directed spinodal decomposition has been identified for first time. Composition stratification with sub-surface segregation of Cr has been explained. Necessity of 11 at% Cr for instantaneous passivation in stainless steels understood. Abstract: A detailed thermodynamic assessment has for the first time shown that the rapid oxide film formation on stainless steels subjected to the natural air atmosphere at room temperature is actually facilitated by " oxygen dissolution induced surface directed spinodal decomposition " in the Fe-Cr-O solid solution. The proposed mechanism has led to a clear explanation of the following until now un-explained observations: i) complete compositional stratification involving a sub-surface segregation of Cr atoms within the oxide film on stainless steels; ii) necessity of a minimum of about 11 at.% Cr in stainless steels for rapid passivation characteristics.